Promosi Perpustakaan dalam Upaya Meningkatkan Kunjungan Perpustakaan - Wibawanto, Alwan (Pustakaloka, 2009)
Library is one the information sources with an ability to comprise knowledge, technology, art, and culture. It is also an institution that has democratic, economic and strategic position to make endeaver to educate nation and play a role as an instrument to conduct an active learning as well as long life education lifelong learning for either individual or collective.